Anemia ferropénica y su relación con el desarrollo en niños de 6 a 36 meses de edad que acuden al Centro de Salud N° 1 de la ciudad de Loja. - Pontón Gaona, Marcia Judith (2017)
During childhood Iron deficiency is very common. This period is characterized by the hippocampus, the maximum development in the regional cortical, by myelination and maturation of dendrites, also by accelerated synaptogenesis in the brain. Children with iron deficiency have a lower cognitive development, motor, social-emotional and neurophysiological characteristics than infants with normal levels of iron. Considering that in childhood there is a high risk of iron deficiency due to the high demands of iron for rapid growth and brain development, the present study, which the main objective was to know the relationship between iron deficiency, anemia, and psychomotor development in children aged 6 to 36 months. These children attended the Health Center Nº1 of the city of Loja during the period of July to December 2016. This study includes 166 infants, to whom the Denver Test is applied to evaluate psychomotor development and took the basis of SIVAN (National Food Surveillance System), information regarding the hemoglobin values of each of them. The data was tabulated in the program SPSS IBM 20 Statics obtaining the following results: 48.2% of the children had iron deficiency anemia, of which 45.8% were mild anemia and 2.4% were moderate anemia. As for the psychomotor development, in 21.7% of children, there were doubtful results and in 3.8% an abnormal test was obtained. The area of development most affected was the fine motor that corresponded to 3%. It can be concluded that those children who do not have anemia, have normal development; in those who have mild or moderate anemia, development is affected. Key Words: psychomotor development, ferropenic anemia, infants